PERANAN GURU PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MENGEMBANGKAN KARAKTER SISWA MELALUI AJARAN TRI HITA KARANA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 BANGLI - Widyani, Ni Wayan; Arini, Ni Wayan; Suyeni, Ni Made (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
This research aims to obtain accurate information and an objective overview of the role of Hindu Religious Education and Moral Education teachers in developing students' character through the teaching of Tri Hita Karana, thus providing understanding to the readers about the importance of Hindu religious teachings in developing students' character.This is a qualitative research with a phenomenological approach. The theories used to analyze the problem are the behaviorist theory by Gege and Berliner, character theory by Thomas Lickona, and motivation theory by Abraham Maslow. The subjects of this study are Hindu Religious Education teachers, students, and the Head of State Junior High School 1 Bangli. The data collection methods used are observation, interviews, literature review, and documentation study. The collected data are analyzed using qualitative descriptive analysis with the following steps: data reduction, data presentation, and conclusion drawing.The results of the study indicate that (1) the strategies used by Hindu Religious Education and Moral Education teachers are through the implementation of cooperative learning model with a scientific approach, lecture and discussion methods, and cooperative learning strategies. (2) The character education values developed through the implementation of the teaching of Tri Hita Karana in State Junior High School 1 Bangli include religiousness, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love for the homeland, appreciation of achievement, friendliness (communicative), love for peace, love for reading, concern for the environment, social concern, and responsibility. (3) The impacts of implementing the teaching of Tri Hita Karana on the development of students' character in State Junior High School 1 Bangli are the development of students' character, increased awareness of students to practice their religious teachings, increased students' concern for others, increased students' concern for the environment, and the establishment of harmony